The Impact of Gender on Supervisors’ Perceptions of Employees - Kinowska, Hanna (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2017)
The article examines the impact of gender on how superiors perceive subordinates. The analysis was based on a review of the literature and the results of research on the opinions of subordinates on superiors, done in 2016 by the Institute of Human Capital, Warsaw School of Economics. The causes of pay discrepencies are analysed on the basis of the subject literature, as are the dynamics of women’s participation in top positions in Poland and the European Union. The influence a superior may have on an employee’s career is characterized. What causes programmes aimed at promoting more objective decisions to be ineffective are identified. Based on the results of quantitative research, gender-based differences in the relationships subordinates have with superiors is determined. A key area of divergence were issues pertaining to justice, particularly where the evaluation of employees, the division of tasks and rewards were concerned.